An introduction to digital media research methods: how to research and the implications of new media data. Issue 1 (2nd January 2016) - Hutchinson, Jonathon
ABSTRACT: Digital methods have previously been described as 'a term that seeks to capture a recent development in Internet-related research, summarized as approaches to the web as data set'. Using this as a starting point, this paper positions digital media methods as a methodological approach that incorporates internet-based data, while also including other communicative and social media platforms such as Instagram, Vine, Twitter, giffy, Periscope, and Facebook amongst others. Digital media methods also extends to database research, data generated by sensors, drones and autonomous automobiles. Contemporary research engaging digital media methods is built upon the 'computational turn' where 'computational approaches is increasingly reflected across a number of disciplines, including the arts, humanities and social sciences, which use technologies to shift the critical ground of their concepts and theories'. As media and communication scholars, our 'research is increasingly being mediated through digital technology… affecting both the epistemologies and ontologies that underlie a research program'. This paper highlights three significant points of departure for digital media methods in the media and communication discipline: the increasing need for typologies and ontologies in social media research; the significance of mapping public issues; and the difficulties researchers face as text-based communication shifts to visually oriented platforms.